2018
DOI: 10.1002/anie.201804942
|View full text |Cite
|
Sign up to set email alerts
|

Magnetophoretic Sorting of Single Catalyst Particles

Abstract: A better understanding of the deactivation processes taking place within solid catalysts is vital to design better ones. However, since inter-particle heterogeneities are more a rule than an exception, particle sorting is crucial to analyse single catalyst particles in detail. Microfluidics offers new possibilities to sort catalysts at the single particle level. Herein, we report a first-of-its-kind 3D printed magnetophoretic chip able to sort catalyst particles by their magnetic moment. Fluid catalytic cracki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…In these particles, Fe is most likely deposited as clusters. These Fe clusters were already observed in the study of Solsona et al., in which it was demonstrated that particles with high Fe levels are not necessarily heavily deactivated …”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…In these particles, Fe is most likely deposited as clusters. These Fe clusters were already observed in the study of Solsona et al., in which it was demonstrated that particles with high Fe levels are not necessarily heavily deactivated …”
Section: Resultssupporting
confidence: 68%
“…These Fe clusters were already observed in the study of Solsonae tal.,i nw hich it was demonstrated that particles with high Fe levels are not necessarily heavily deactivated. [18] The different correlations between Fe and Ni with acidity and accessibility,l ead to the question how Fe and Ni relate to each other.F igure 5a shows the Ni-Fe correlation plots as a result of overlaying the single particle XRF maps. The correlation appears to be af an-shaped plot, indicating that particles with high Ni concentrationsg enerally also have elevated Fe levels.T he reversec orrelation,o nt he other hand, does not uphold,m eaning that particles with ah igh Fe concentration do not necessarilyh ave ah igh Ni content as well.…”
Section: Correlations Between Metal Type and Content Andc Atalyst Parmentioning
confidence: 99%
See 1 more Smart Citation
“…These actuators can be based on various phenomena, but the most commonly used are electric field, 191,197,200 mechanic valves, 189,190,194,201 temperature, 202,203 acoustic waves, 204 pressure, 195,205 and magnetic field. [206][207][208] Particle storage and tagging. Catalyst deactivation over time is of great concern for researchers and industry.…”
Section: Perspectives On Catalyst Characterization In Microfluidicsmentioning
confidence: 99%
“…These actuators can be based on various phenomena, but the most commonly used are electric field, 162,168,171 mechanic valves, 160,161,165,172 temperature, 173,174 acoustic waves, 175 pressure, 166,176 magnetic field. [177][178][179]…”
Section: Single Particle Sortingmentioning
confidence: 99%